Correction: Hidden ordered structure in the archetypical Fe(pyrazine)[Pt(CN)4] spin-crossover porous coordination compound. Issue 44 (3rd November 2022) - Fernández-Blanco, Ángel; Mariano, Lorenzo A.; Piñeiro-López, Lucía; Real, José Antonio; Costa, Jose Sanchez; Poloni, Roberta; Rodríguez-Velamazán, J. Alberto
Abstract : Correction for 'Hidden ordered structure in the archetypical Fe(pyrazine)[Pt(CN)4 ] spin-crossover porous coordination compound' by Ángel Fernández-Blanco et al., CrystEngComm, 2022, 24, 6349–6356, ; https://doi.org/10.1039/D2CE00895E .